Wireless sensor network accurate TOA location algorithm based on the energy detection. (2016) - Wang, Hong-Bin; Feng, Li-Ping; Cao, Jian-Fang; Liu, Chan
To further improve the localisation accuracy based on the energy detection, this paper combined the TMMR-TC algorithm with the MUSIC algorithm, and proposed a two-step TOA estimation algorithm. The peak search of the MUSIC algorithm was done in the search range provided by TMMR-TC algorithm. Through the comparison between the two-step algorithm and several other algorithms, it is found that the two-step method accuracy has been significantly improved, and it has achieved great positioning performance in the whole SNR range.